2004
DOI: 10.1161/01.cir.0000141726.01302.83
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Heart Failure Among Women With Coronary Disease

Abstract: Background-Although heart failure is common among women with coronary disease, the risk factors for developing heart failure have not been well studied. We determined the risk factors for developing heart failure among postmenopausal women with established coronary disease. Methods and Results-This is a prospective cohort study using data from the Heart and Estrogen/progestin Replacement Study (HERS), a randomized, blinded, placebo-controlled trial of 4.1 years' duration, and subsequent open-label observationa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
84
0
2

Year Published

2006
2006
2016
2016

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 152 publications
(90 citation statements)
references
References 44 publications
4
84
0
2
Order By: Relevance
“…Incident heart failure was defined as hospitalizations to treat either increased intravascular volume or low cardiac output that was because of cardiac disease. 16 We classified the severity of incident heart failure as requiring either 1 hospitalization during the follow-up period or Ն2 hospitalizations. Finally, incident MI was also included as an adjustment variable.…”
Section: Secondary Predictorsmentioning
confidence: 99%
“…Incident heart failure was defined as hospitalizations to treat either increased intravascular volume or low cardiac output that was because of cardiac disease. 16 We classified the severity of incident heart failure as requiring either 1 hospitalization during the follow-up period or Ն2 hospitalizations. Finally, incident MI was also included as an adjustment variable.…”
Section: Secondary Predictorsmentioning
confidence: 99%
“…L eft ventricular (LV) hypertrophy (LVH), whether determined by the ECG [1][2][3][4][5][6][7][8][9] or echocardiogram, 6 -8,10 -18 has been associated with various adverse cardiovascular outcomes, including mortality, myocardial infarction, and heart failure. Although there has been considerable speculation as to why LVH is such an important marker of risk, 19,20 the basic mechanisms that predispose patients with LVH to develop atherosclerotic heart disease (ASHD) are not known.…”
mentioning
confidence: 99%
“…2,10,15,18,19 Diabetes appears to be a particularly strong risk factor for the development of HF in women. 1,20 The investigation of outcomes in women with HF has been limited by the smaller proportion of women (17%-23%) than men enrolled in clinical trials. 4 Of the two most common causes of death in patients with HF, progressive HF and sudden cardiac death (SCD), men are more likely than women to die from SCD.…”
Section: Morbidity and Mortalitymentioning
confidence: 99%
“…A few observational studies suggested that this subpopulation may actually benefit with HRT, but randomized studies are conflicting. 20,55,56 Several HF-specific benefits of estrogen are noted. For instance, afterload reduction via the vasodilatory properties of estrogen can theoretically improve outcomes in HF.…”
Section: Hf Therapiesmentioning
confidence: 99%